Psychosocial care in dementia in European higher education: Evidence from the SiDECar ("Skills in DEmentia Care") project. (August 2021) - Ottoboni, G.; Chirico, I.; Povolná, P.; Dostálová, V.; Holmerová, I.; Janssen, N.; Dassen, F.; de Vugt, M.; Sánchez-Gómez, Ma.C.; García-Peñalvo, F.; Franco-Martin, M.A.; Chattat, R.
Abstract: In dementia care, psychosocial interventions can increase people's quality of life with dementia and their caregivers. Despite their effectiveness, their translation into practice lacks the desirable systematicity. Systematic educational programs on psychosocial interventions in dementia will improve this translation, as it prepares professionals to face the complexity of dementia care. This study aimed to systematically map out the extent to which higher education programs in Europe include teaching activities about psychosocial care of dementia. We collected quantitative and qualitative data about 303 higher education teaching activities on psychosocial care in dementia across Europe. The analysis revealed that the number of teaching activities focusing on psychosocial care in dementia was relative. Although the results reflected UNESCO indications, the teaching activities on psychosocial care in dementia appeared less systematized than optimal. As world health agencies recommend, international higher education systems should consider more psychosocial care topics because they can prepare professionals to respond timely and effectively to dementia patients and caregivers' needs.